Putative synaptic mechanisms of inhibition in Limulus lateral eye (The Rockefeller University Press, 1976)
Serotonin (5-HT) perfusion of a thin section of Limulus lateral eye hyperpolarizes retinular and eccentric cell membrane potential, and blocks spike action potentials fired by the eccenteric cell. The indoleamine does not directly affect retinular cell receptor potential or eccenteric cell generator potential in response to light stimuli. LSD perfusion blocks both this inhibitory action of 5-HT and light- evoked, synaptically mediated, lateral inhibition. Iontophoretic application of 5-HT to the synaptic neuropil produces shorter latency and duration and larger amplitude of inhibition than does the perfusion technique. This inhibition is dose dependent; the accompanying inhibitory postsynaptic potential (IPSP) appears to have an equilibrium potential more hyperpolarized than normal resting potential levels of ca. -50 mV. IPSP amplitude is sensitive to extracellular potassium ion concentration: it increases with decreased [K+]0 and decreases with increased [K+]0. LSD blocks the inhibition produced by iontophoretic application of 5-HT. Interaction between light-evoked, natural synaptic transmitter-mediated IPSP's and 5-HT IPSP's suggests a common postsynaptic receptor or transmitter-receptor-permeability change mechanism.